Functional and Structural Characterization of a Novel HLA-DRB1*04:01-Restricted α-Enolase T Cell Epitope in Rheumatoid Arthritis - Gerstner, Christina; Dubnovitsky, Anatoly; Sandin, Charlotta; Kozhukh, Genadiy; Uchtenhagen, Hannes; James, Eddie A.; Rönnelid, Johan; Ytterberg, Anders Jimmy; Pieper, Jennifer; Reed, Evan; Tandre, Karolina; Rieck, Mary; et al. (Frontiers in Immunology, 2016)
Antibodies to citrullinated proteins, common in Rheumatoid Arthritis (RA) patients, are strongly associated to a specific set of HLA-DR alleles including HLA-DRB1*04:01, *04:04 and *01:01. Here, we first demonstrate that autoantibody levels towards the dominant citrullinated B cell epitope from α-enolase are significantly elevated in HLA-DRB1*04:01-positive RA patients. Furthermore, we identified α-enolase-derived T cell epitopes and demonstrated that native and citrullinated versions of several peptides bind with different affinities to HLA-DRB1*04:01, *04:04 and *01:01. The citrulline residues in the eight identified peptides are distributed throughout the entire length of the presented epitopes and more specifically, localized at peptide positions p-2, p2, p4, p6, p7, p10 and p11. Importantly, in contrast to its native version peptide 26 (TSKGLFRAAVPSGAS), the HLA-DRB1*04:01-restricted citrullinated peptide Cit26 (TSKGLFCitAAVPSGAS) elicited significant functional T cell responses in primary cells from RA patients. Comparative analysis of the crystal structures of HLA-DRB1*04:01 in complex with peptide 26 or Cit26 demonstrated that the post-translational modification did not alter the conformation of the peptide. And since citrullination is the only structural difference between the two complexes this indicates that the neo-antigen Cit26 is recognized by T cells with high specificity to the citrulline residue.